Evaluation of Head Position in Static and Dynamic Three-Dimensional Imaging: a review of the Literature - Marie Kjærgaard Larsen; Torben H. Thygesen (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Background: The interest in three-dimensional imaging in orthognathic treatment planning has been growing, especially for evaluation of the natural head position. Several three-dimensional devices are available on the market. Three-dimensional evaluation of the patient will probably soon be a standard tool/method in orthognathic treatment planning. Purpose: The purpose of the study was a clarifi cation of the literature for studies regarding the natural head position in three-dimensional imaging. Materials and methods: A systematic search of the literature was conducted through PubMed to identify studies that evaluate head positions in three-dimensional imaging. Following search syntax was used: "3d imaging", "three-dimensional", "natural head position", and "imaging head position". Results: Only four studies have investigated the reproducibility and accuracy of head positions in three-dimensional imaging. The studies show that the natural head position is reproducible with the use of three-dimensional photography. Conclusion: Three-dimensional imaging to register the natural head position in orthognathic treatment planning shows promising results. Only four studies have evaluated its reproducibility. Future studies regarding its accuracy and reproducibility are essential.